Saint Bridget of Sweden and the Teutonic Knights. Her Revelations in the context of the Gothic crucifix from the Holy Trinity Cathedral in Kulmsee (Chełmża) and the legacy of other mystics - Waszak, Przemysław (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2022)
The article presents an analysis of the early fifteenth-century wood-carved crucifix from the Holy Trinity cathedral in Kulmsee (Chełmża) in the context of the fourteenth-century Brigidian Revelations. The crucifix was created in a unique in the Teutonic Order State four-nails type. It differs from other, more distant, and older, crucifixes of the four-nails type. In my opinion, the crucifix, because of its inspirations which come from the Revelations of Saint Bridget of Sweden, is another type of a mystical work of art; however, it does not belong to the fourteenth-century widespread type of mystical, extremely suffering crucifixes. My intention is to show that the reception of ideas and motifs in the Gothic times could also be apolitical, although it might be considered a paradox since we have in mind some critical remarks of Saint Bridget towards the Teutonic Order. Furthermore, I emphasise that in the fourteenth century, which was a period distinguished by flourishing mysticism, were present certain similarities in writings of various mystics, which can be compared to a style of the particular time – in German, “Zeitstil”. The discussed crucifix is another evidence that in Christian art the sculptors and their instructors had tremendous artistic licence, and the sacred image along with its visual language was of significant importance for the piety of that period.